2013
DOI: 10.1111/ajco.12079
|View full text |Cite
|
Sign up to set email alerts
|

Neuro‐oncology practices in Australia: A Cooperative Group for Neuro‐Oncology patterns of care study

Abstract: Aims To provide data on the patterns of care in neuro‐oncology practices at Australian cancer centres over the previous 12‐month period. Methods A 5‐page questionnaire was sent to Cooperative Trials Group for Neuro‐Oncology members at 28 Australia cancer centres. The questions included access to neuro‐oncology services; treatment protocols and patterns of supportive care. Results Provision of neuro‐oncology services was consistent in metropolitan cancer centres. Treatment protocols are virtually identical for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…7,8 Dexamethasone once a day is the preferred corticosteroid based on side-effect profile, but still has a wide range of side-effects (e.g., Cushing effect, muscle weakness and diabetes mellitus), increasing with higher dose and longer duration of treatment. 9,10 A randomized controlled trial (RCT) on the use of dexamethasone in brain tumours indicated that an effective starting dose is 4 mg/day, with a maximum effective dose of 16 mg/day for symptom control.…”
Section: Pain/headachementioning
confidence: 99%
“…7,8 Dexamethasone once a day is the preferred corticosteroid based on side-effect profile, but still has a wide range of side-effects (e.g., Cushing effect, muscle weakness and diabetes mellitus), increasing with higher dose and longer duration of treatment. 9,10 A randomized controlled trial (RCT) on the use of dexamethasone in brain tumours indicated that an effective starting dose is 4 mg/day, with a maximum effective dose of 16 mg/day for symptom control.…”
Section: Pain/headachementioning
confidence: 99%
“…The majority of patients with glioblastoma are managed in the public sector. The initial treatment of glioblastoma closely adheres to the Stupp protocol, which is a combined modality strategy consisting of maximal safe neurosurgery, then radiotherapy with concomitant and adjuvant temozolomide (11). Neurosurgery is typically performed by subspecialist brain tumor surgeons in major cities.…”
Section: Clinical Managementmentioning
confidence: 99%
“…Following neurosurgery, most cases are presented at neuro-oncology multidisciplinary meetings, which are convened in about 81% of subspecialty cancer centers (11). This facilitates review of the integrated diagnosis of glioblastoma and treatment planning, as well as discussion of subsequent management dilemmas such as suspected pseudoprogression, the role of repeat resection and/or reirradiation at relapse.…”
Section: Clinical Managementmentioning
confidence: 99%
See 2 more Smart Citations